2017
DOI: 10.3928/01477447-20161108-03
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Unconstrained Primary Total Hip Arthroplasty in Ipsilateral Residual Poliomyelitis

Abstract: Incapacitating articular sequelae in the hip joint have been described for patients with late effects of poliomyelitis. In these patients, total hip arthroplasty (THA) has been associated with a substantial rate of dislocation. This study was conducted to evaluate the long-term clinical and radiologic outcomes of unconstrained THA in this specific group of patients. The study included 6 patients with ipsilateral polio who underwent primary THA between 1985 and 2006. Patients with polio who underwent THA on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Their component revision rate at 6-year follow-up was 5.1%, with osteolysis (10.2%) and dislocation (5.1%) being the most commonly encountered complications. A further 8 retrospective case series with a total of 78 THAs also reported improved functional outcomes through a variety of scoring systems, [ [56] , [57] , [58] , [59] , [61] , [62] , [63] , [64] ] which are detailed in Figure 5 .
Figure 5 Total hip arthroplasty in poliomyelitis results.
…”
Section: Resultsmentioning
confidence: 99%
“…Their component revision rate at 6-year follow-up was 5.1%, with osteolysis (10.2%) and dislocation (5.1%) being the most commonly encountered complications. A further 8 retrospective case series with a total of 78 THAs also reported improved functional outcomes through a variety of scoring systems, [ [56] , [57] , [58] , [59] , [61] , [62] , [63] , [64] ] which are detailed in Figure 5 .
Figure 5 Total hip arthroplasty in poliomyelitis results.
…”
Section: Resultsmentioning
confidence: 99%
“…Given that instability/dislocation remains one of the most common complications of THA, some authors have suggested that constrained liners (CL) may be associated with higher loosening rates in the long term [35]. However, Ryu et al have shown that both CL and dual-mobility (DM) liners efectively reduce the risk of hip dislocation in elderly patients with neuromuscular diseases, including CP [36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Edwards et al[ 18 ] suggested that using MHSS instead of HHS is adequate for determining functional outcomes after primary and revision THA. Recent studies related to primary or revision THA have reported their results with MHHS,[ 23 , 24 ] which appears to be more practical than HHS and may help save the surgeon’s time in an outpatient clinic. In the present study, there was a very strong correlation between HHS and MHHS in both, primary and revision THA.…”
Section: Discussionmentioning
confidence: 99%